Semiconducting properties of passive films and corrosion layers on weathering steel. (10th September 2020) - Tranchida, G.; Franco, F. Di; Megna, B.; Santamaria, M.
Highlights: Anodic film on Weathering Steel are n-type semiconductor with band gap of 2 eV. Rust layers on Weathering Steel were grown by atmospheric corrosion. Rust layers mainly contain magnetite and lepidocrocite. Rust layers behave as n-type semiconductor with band gap between 2.3 and 2.6 eV. Mott-Schottky theory is not suitable to model the measured differential capacitance. Abstract: Anodic films were grown on Weathering Steel by potentiostatic polarization in slightly alkaline solution. The photoelectrochemical results reveal that they are n-type iron oxide with Eg  = 2.0 eV. Rust layer grown by atmospheric corrosion are n-type semiconductors with a band gap higher than that estimated for the anodic film attributed to the formation of γ-lepidocrocite. The electrochemical impedance spectra allow to evidence that rust layers have a higher conductivity with respect to anodic films due to the presence of highly doped iron oxide layers. The use of Mott-Schottky theory to model the dependence of oxide capacitance as function of potential is critically discussed.